Prevalence and main factors influencing anxiety symptoms in Chinese older adults with cataracts: a national cross-sectional survey - Fadong Zhang; Xiang Li; Ketong Liu; Lanzhi Xie; Lu Wan; Shiwei Cao; Yandi Fu; Tengfei Niu (Frontiers in Psychiatry)
BackgroundThe mental health of cataract patients should not be ignored; however, little is known from existing studies about anxiety symptoms in Chinese older adults with cataracts. The aim of this study was to assess the prevalence of anxiety symptoms and their key influencing factors among Chinese older adults with cataracts.MethodsBased on the cross-sectional data published in 2018 by the Chinese Longitudinal Healthy Longevity Survey (CLHLS), 1,320 cataract patients aged 65 and older were finally included. Anxiety symptoms were assessed using the Generalised Anxiety Disorder (GAD-7) scale. Logistic regression analyses were performed on 24 variables from three dimensions: socio-demographic characteristics, health status and lifestyle, in order to investigate the influencing factors of anxiety symptoms in older adults with cataracts. Meanwhile, this study developed an advanced Random Forest Model to rank the importance of the significant influencing factors in the logistic regression, providing an in-depth understanding for further precision prevention and management.ResultsThe prevalence of anxiety symptom in Chinese older adults with cataracts was 11.06%. Logistic regression analyses showed that poor economic status (OR=3.162, 95% CI:1.719-5.817), obesity(Body Mass Index>28) (OR=2.11,95%CI:1.10-4.05), poor self-reported health (OR=1.91,95%CI:1.11-3.30), sleeping less than 7h(OR=1.98,95%CI:1.30-3.01), having fair (OR=1.61,95%CI:1.03-2.53) or poor (OR=2.70,95%CI:1.21-6.02) life satisfaction, and having hearing impairment (OR=1.72,95%CI:1.12-2.65) were risk factors for anxiety symptoms in cataract patients, eating fresh fruits (OR=0.587, 95%CI:0.369-0.933) and age (OR=0.97,95%CI:0.94-0.99) were protective factors for anxiety symptoms in cataract patients. The results of Random Forest showed that age was the most important factor affecting anxiety symptoms in cataract patients, followed by Body Mass Index, self-reported health, economic status, eating fruits or not, sleep duration, life satisfaction, and hearing impairment.ConclusionThe results of the study showed that the anxiety symptoms of cataract patients should not be ignored and are influenced by a variety of factors. Healthcare workers should actively conduct mental health screening and strengthen the monitoring of important influencing factors in the treatment and care of cataract patients.